Tinjauan Hukum Islam Pada Tradisi Pemberian Jeulamee Saat Khitbah Di Mukim Lamreung Aceh Besar - Mustolih, Ahmad; Purnomo, Ridho (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study examines the practice of giving jeulamee (dowry) during engagement (khitbah) in Mukim Lamreung, Krueng Barona Jaya District, Aceh Besar, from an Islamic legal perspective. Normatively, dowry is a husband’s obligation after the marriage contract, but in Lamreung’s tradition, part of the dowry is given during the engagement as a symbol of sincerity and commitment. This research employs a qualitative descriptive method through observation and interviews with local community, religious, and customary leaders. The findings reveal that the giving of jeulamee during khitbah is viewed as a valuable social tradition but, in Islamic law, is classified as a gift (hibah), not a valid dowry. The Aceh Ulama Consultative Council (MPU) Fatwa No. 5 of 2016 states that property given during engagement is considered a gift and must be returned if the marriage does not occur. Therefore, this tradition is acceptable as long as it is understood as a cultural practice consistent with Islamic legal principles rather than a religious obligation.